Zooming-in on the proteome: very narrow-range immobilised pH gradients reveal more protein species and isoforms. - Westbrook, J; Yan, J; Wait, R; Welson, S; Dunn, M (2001)
Two-dimensional gel electrophoresis (2-DE) enables separation of complex mixtures of proteins on a single polyacrylamide gel according to isoelectric point, molecular weight, solubility, and relative abundance. For this reason, 2-DE together with mass spectrometry (MS) has become a key technology in proteome analysis. The introduction of immobilised pH gradients (IPGs) for isoelectric focusing of proteins affords improved reproducibility and permits full-scale proteome analyses to be undertaken. Whilst broad-range IPGs are useful for investigating simple proteomes (e.g. Mycoplasma genitalium) it is becoming clear that additional resolving power is needed for separating the more complex proteomes of eukaryotic organisms. The use of narrow-range and very narrow-range IPGs provides the means with which to dissect a complex proteome. We have compared very narrow-range IPGs (3.5-4.5L, 4-5L, 4.5-5.5L, 5-6L, and 5.5-6.7L) with broad- (3-10NL) and narrow-range IPGs (4-7L and 6-9L) for the visualisation of the human heart proteome. The superior ability of very narrow-range IPGs to separate different protein species and isoforms, compared with 3-10NL and 4-7L 2-D gels is demonstrated. The results are supported by MS identifications which further show that reduction of the number of comigrating protein species results in less ambiguous and more reliable database search results.